2022
DOI: 10.1093/ckj/sfac155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kidney replacement therapy modality after first kidney graft failure on second kidney transplantation outcomes

Abstract: Background There is lack of information regarding which is the best dialysis technique after kidney transplant (KT) failure. The aim of this study is to compare the effect of kidney replacement therapy modality -peritoneal dialysis (TX-PD-TX), hemodialysis (TX-HD-TX) and preemptive deceased donor retransplantation (TX-TX)- on patient survival and second KT outcomes. Methods A retrospective observational study from the Catalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…A prior cohort study of patients with failed first allografts showed that patients reinitiated on dialysis and on the waitlist for repeat transplantation post-allograft loss had superior survival compared to patients reinitiated on dialysis but not waitlisted, likely reflecting differences in patient characteristics and comorbid burden [ 26 ]. Similarly, our study has shown that patients who were waitlisted for repeat transplantation following first allograft loss had significantly lower risk of all-cause mortality compared to patients who were not waitlisted, with this survival advantage observed for those with or without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A prior cohort study of patients with failed first allografts showed that patients reinitiated on dialysis and on the waitlist for repeat transplantation post-allograft loss had superior survival compared to patients reinitiated on dialysis but not waitlisted, likely reflecting differences in patient characteristics and comorbid burden [ 26 ]. Similarly, our study has shown that patients who were waitlisted for repeat transplantation following first allograft loss had significantly lower risk of all-cause mortality compared to patients who were not waitlisted, with this survival advantage observed for those with or without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that patients on PD have comparable (or better) clinical outcomes and quality of life as patients on HD [ 2 , 4 , 5 , 7 , 28 ]. In addition, PD is generally less expensive than HD, making this RRT a cost-effective option for ESKD patients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Large observational studies indicate a survival advantage of PD for the initial 2–3 years of therapy, with subsequent loss of this benefit or later advantage to HD. Moreover, PD may offer some advantages over HD with regard to quality of life and kidney transplantation outcome [ 4 , 5 ] and costs savings [ 1 ]. Ideally, the individual choice for the most appropriate dialysis modality should be made following an evidence-based approach considering patient characteristics and needs, current and future options for renal replacement therapy (RRT), and patient preferences.…”
Section: Introductionmentioning
confidence: 99%